ASPEK PIDANA DAN HUKUM LINGKUNGAN UNDANG UNDANG NO 3 TAHUN 2020 TENTANG PERTAMBANGAN MINERAL DAN BATUBARA - Yuliawati, Irma; Masyhar, Ali (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2021)
Mining is one of the assets owned by the State of Indonesia, as a natural resource with enormous potential. With this fact, making Indonesia glimpsed by many investors, both from within the country and abroad. The government as a stakeholder in all affairs, including in the management and utilization of minerals and other produce, made a policy with the issuance of Law No. 3 of 2020 amending Law No. 4 of 2009 on Mineral and Coal Mining. With the presence of the Law, there are several regulations that change due to the formation process that is influenced by politics. The role of politics and power is very evident with the passing of the Minerba Law at an insanity time, namely at a time when the Covid-19 outbreak is rampant in all corners of the world, including in Indonesia. In terms of the process of its formation, there is not much struggle in terms of substance so as to show the existence of agreement in all members of the House of Representatives, each of which has Interests. Another thing that becomes a problem is in terms of criminal provisions contained in this Law which is even more detrimental to the surrounding community even the environmental impact that occurs after mining.